(untitled) (Ustozlar uchun, 2026)
The progression of Uzbekistan’s football to the World Cup is not a process measured by the actions of 22 players on the pitch. It is the collective breath of thousands of people in the stands, the transformation of fan culture, and the projection of national self-awareness in stadiums. We often associate victories with tactics and coaching skill, but without the "12th player" factor, the modern football system cannot function fully. In the mid-2000s, for fans of Uzbek football, the stadium was "just a viewing arena". General shouts of "forward," noise, and emotional pressure focused on the result rather than the process of the game prevailed there.